Pre-evaluation of strong base anion exchange, Amberlite IRA 958-Cl resin for nitrate removal - Norhayati, Abdullah; Rosmaizah, Muhammad; Aimi Asyiqin, Abu Kassim (Elsevier Ltd, 2019)
High concentration of nitrate in water either in surface or groundwater is an effect from agricultural activities, domestic use and industrial activities. Hence, removing enormous nitrate from water is necessary because it hazardous to the human health and aquatic life. The ion exchange resin is the most widely technology used in removing nitrate from water source. In this study, commercial strong anion exchange resin, Amberlite IRA 958 was used to study the efficiency of nitrate removal from aqueous solution in a fixed-bed column experiment. The influence of resin dosage (0.05 to 0.20 g), contact time (1 to 4 hours) and initial nitrate concentration (20, 50, 100 and 200 mg/L) were examined. More than 87% of nitrate removal achieved at 0.1 g of resin dosage, 3 hours of contact time and 20 mg/L of initial nitrate concentration. This promising result make that Amberlite IRA-958 can become an attractive candidate as adsorbent for nitrate removal.